KEMAMPUAN MEMBACA PEMAHAMAN ISI RUPAMA SISWA KELAS VIII SMP NEGERI 1 MANGARABOMBANG KABUPATEN TAKALAR: READING COMPREHENSION ABILITY OF RUPAMA CONTENT OF GRADE VIII STUDENTS OF SMP NEGERI 1 MANGARABOMBANG TAKALAR DISTRICT - Nurhikma; Syamsudduha; Hajrah (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
The purpose of this study is to describe the reading comprehension ability of rupama content of class students. This research is a quantitative descriptive research. The population of this study included all VIII grade students of SMP Negeri 1 Mangarabombang Takalar Regency totalling 326 students. The sample determination in this study used Krejcie Morgan theory with a sample of 177 students. The technique used in data collection in this study was a multiple choice test totalling 25 numbers. The data obtained were analysed using quantitative descriptive analysis. The results showed that students who scored 86-100 were 5 people (3%) categorised as very capable, students who scored 75-85 were 20 people (11%) categorised as capable, students who scored 70-74 were 5 people (3%) categorised as less capable and students who scored 0-69 were 147 people (83%). Thus, it can be stated that the ability to read comprehension of Rupama content of students in class VIII of SMP Negeri 1 Mangarabombang Takalar Regency is categorised as unable